Do FDI determinants converge across regions? Evidence from two Indonesian provinces - M. Afdal Samsuddin; Ary Fakturrachman Aryansyah; Rowiyah Asengbaramae (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2026)
This study examines whether foreign direct investment (FDI) responses are region-specific or follow broader economic patterns, using empirical evidence from West Sumatra and the Special Region of Yogyakarta (SRY). Despite having different economic structures, with West Sumatra being commodity-based and SRY being service-oriented, both provinces provide an important context for analysing the convergence of regional FDI determinants. Using a Vector Error Correction Model (VECM) and impulse-response analysis on quarterly data from 2010 to 2023, this study finds partial convergence in the FDI determinants. The results show that both provinces respond to common macroeconomic variables, including inflation, economic growth, minimum wages, and exports; however, the direction and magnitude of these effects differ across regions. In West Sumatra, economic growth and export expansion do not necessarily increase FDI inflows, reflecting structural characteristics of a commodity-based economy. Conversely, economic growth strengthens FDI attractiveness in SRY, while higher labour costs reduce investment inflows. These findings suggest that both general macroeconomic conditions and region-specific economic structures shape FDI determinants. This study contributes to the literature by highlighting partial convergence and regional heterogeneity in the determinants of FDI across structurally different regions in Indonesia.